EFEKTIVITAS MODEL PEMBELAJARAN QUANTUM DENGAN MICROSOFT KAIZALA TERHADAP HASIL BELAJAR OPERASI HITUNG - Ike Kuswardani; Nunuk Suryani; Yumiati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
Mathematics reflects students' reasoning and is determined by the use of learning models used by teachers. The research described in this article aims to describe the effectiveness of quantum learning models with Microsoft Kaizala on students’ learning outcomes of integer counting operations at grade IV elementary school. The method used in the research was a quasi-experimental research method with a nonequivalent control group design. The research samples involved 30 sixth-grade students of SDN 1 Ngadirejo, 36 sixth-grade students of SDN 2 Ngadirejo, and 18 sixth-grade students of SDN 4 Ngadirejo. Data were collected by using a test technique and then analyzed by using a t-test with a significance level of α = 0.05. Based on the calculation, it was obtained that thitung was 13.162 with a p-value of 0.000<0.05. Thus, it could be concluded that a quantum learning model with Microsoft Kaizala was effectively improving the students’ learning outcomes of the integer counting operations at the grade VI level. The quantum learning model with the TANDUR structure could maximize students’ learning activity so that the learning environment and interaction that occurred established a foundation and framework for learning.